Radical enhancement as a moral status de-enhancer - Gray, Jesse, author; Gorin, Moti, advisor; MacKenzie, Matthew, committee member; Rhodes, Matthew, committee member (Colorado State University. Libraries, 2020)
Human enhancement has worried many thinkers. Some have focused on the potential harms that may befall us, should we walk the path of enhancement. One such harm may be that enhancements serve to undermine our unique human dignity. I argue that the concept of human dignity is better replaced by that of moral status. Others have worried that radical enhancements—those enhancements that give us abilities greatly outside our species typical functioning will lead to a new moral status. I argue that the sorts of enhancements we are likely to seek, namely direct mental state control, will give us reason to think the enhanced will have a moral status subordinate to our own. Finally, I argue that despite the radically enhanced not existing, we still have obligations to create them. I call this the competing known identity problem. Assuming some persons will exist in the future, we have reasons to create the best versions of these persons.
Keywords: moral status; vulnerability; optogenetics; human enhancement